Direct laser writing of copper and copper oxide structures on plastic substrates for memristor devices. (1st March 2023) - Jones, Joshua; Snowdon, Monika R; Rathod, Shasvat; Peng, Peng
Abstract: Rapid fabrication of flexible electronics is attracting much attention in many industries. There is a need to rapidly produce flexible electronic components without relying on costly precursor materials and complex processes. This work presents a direct laser writing (DLW) process capable of rapidly depositing flexible copper or copper oxide structures with a high degree of control over electrical properties. The DLW process uses a low-power fiber laser beam to selectively irradiate a thin film of copper ions to form and interconnect copper nanoparticles. The electrical properties of the deposited patterns can be controlled by tuning laser power, scanning speed, and beam defocus. The microstructures of patterns printed at varying laser powers are investigated using scanning electron microscopy, x-ray photoelectron spectroscopy, and x-ray powder diffraction and the relation between laser power and sheet resistance is explored. The results showed that high laser energy densities resulted in highly conductive patterns of metallic copper, whereas lower energy patterns resulted in copper oxide-rich patterns with significantly lower conductivity. This method can produce high-quality flexible electronic components with a range of potential applications, as demonstrated by the proof-of-concept fabrication of a flexible memristive junction with resistive switching observed at ±0.7 V and a R on / R off ratio of 10 2 .